2013
DOI: 10.1186/1475-2859-12-57
|View full text |Cite
|
Sign up to set email alerts
|

Homofermentative production of optically pure L-lactic acid from xylose by genetically engineered Escherichia coli B

Abstract: BackgroundPolylactic acid (PLA), a biodegradable polymer, has the potential to replace (at least partially) traditional petroleum-based plastics, minimizing “white pollution”. However, cost-effective production of optically pure L-lactic acid is needed to achieve the full potential of PLA. Currently, starch-based glucose is used for L-lactic acid fermentation by lactic acid bacteria. Due to its competition with food resources, an alternative non-food substrate such as cellulosic biomass is needed for L-lactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…plantarum [55] At pH 3.8: 2.6-fold increase in cell growth; Titer -3.1-fold increase, Productivity -5.77AE0.05 g/l/h Lb. rhamnosus [31] Carbon source Xylose to produce L(+)-lactic acid Purity -99.5%, Titer -62.0 g/l, Yield -97.0%, Productivity -1.631 g/l/h (Xylose fermentation) E. coli [49] Sucrose to produce D(S)-lactic acid Titer -110 g/l, Yield -73.0%…”
Section: Metabolic Engineering Solutions To Challengementioning
confidence: 99%
See 1 more Smart Citation
“…plantarum [55] At pH 3.8: 2.6-fold increase in cell growth; Titer -3.1-fold increase, Productivity -5.77AE0.05 g/l/h Lb. rhamnosus [31] Carbon source Xylose to produce L(+)-lactic acid Purity -99.5%, Titer -62.0 g/l, Yield -97.0%, Productivity -1.631 g/l/h (Xylose fermentation) E. coli [49] Sucrose to produce D(S)-lactic acid Titer -110 g/l, Yield -73.0%…”
Section: Metabolic Engineering Solutions To Challengementioning
confidence: 99%
“…casei [48] Carbon source Xylose to produce L(+)-lactic acid Purity -99.5%, Titer -62.0 g/l Yield -97.0%, Productivity -1.631 g/l/h (Xylose fermentation) E. coli [49] Glycerol to produce D(S)-lactic acid Purity -99.97%, Titer -100.3 g/l Yield -78.0%, Productivity -2.78 g/l/h (Glycerol fermentation) E. coli [17] Glycerol to produce L(+) lactic acid Purity -99.9%, Titer -50 g/l Yield -93.0%, Productivity -1.3 g/l/h (Glycerol fermentation) E. coli [16] Xylose to produce L(+)-lactic acid Purity -99.6%, Titer -50.1 g/l, Yield -94.6% (Xylose fermentation) L. lactis [39] Corn starch to produce D(S)-lactic acid Purity -99.6%, Titer -73.2 g/l Yield -0.85 g per g of consumed sugar Productivity -3.86 g/l/h (Starch fermentation)…”
Section: Metabolic Engineering Solutions To Challengementioning
confidence: 99%
“…Multiple rounds of sub-cultivation evolved strain WL204 with improved anaerobic cell growth. WL204 strain produced 62 g/l L-LA (99.5% optical purity) from 70 g/l xylose at 1.63 g/l/h with a yield of 97% based on metabolized xylose (Zhao et al, 2013).…”
Section: Lactic Acid Production By Bacteriamentioning
confidence: 99%
“…Nevertheless, most studies reported the D-lactic acid production from glucose and/or sucrose by an engineered E. coli strain, with a titer, productivity and yield of 80–120 g L −1 , 2–6 g L −1 h −1 and 80–95 %, respectively. Few of these strains, however, have the ability to ferment xylose into D-lactic acid with a desired titer, yield and rate [3, 23, 24, 30, 31]. Furthermore, none, if any, of these strains have demonstrated the ability to co-metabolize both glucose and xylose for enhanced D-lactic acid fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we report reengineering E. coli WL204 (Δ frdBC Δ ldhA Δ ackA Δ pflB Δ pdhR ::pflBp6-acEF-lpd Δ mgsA Δ adhE , Δ ldhA :: ldhL ) [30] for D-lactic acid production by 1) replacing the L-lactate dehydrogenase gene ( ldhL ) with a D-lactate dehydrogenase gene ( ldhA ); 2) eliminating catabolite repression via deletion of the ptsG gene that encodes for IIBC glc , a major enzyme of the glucose PTS system; 3) adaptive evolution in screw-cap tubes for improved cell growth with glucose as the sole substrate. The resulting strain, E. coli JH15, is able to co-utilize both glucose and xylose for enhanced D-lactic acid production.…”
Section: Introductionmentioning
confidence: 99%